TIME SERIES ANALYSIS OF ONION PRODUCTION IN BANGLADESH - HOSSAIN, MOHAMMED MOYAZZEM; Abdulla, Faruq; Parvez, Imran (Innovare Journal of Agricultural Sciences, 2017)
Onion is one of the most important spices in Bangladesh. It's rank top in respect of production and second in terms of area among the spices crops grown in Bangladesh. The main purpose of this research is to identify the Auto-Regressive Integrated Moving Average (ARIMA) model that could be used to forecast the production of onion in Bangladesh. This study considered the published secondary data of yearly onion production in Bangladesh over the period 1971 to 2013. The best selected Box-Jenkins ARIMA model for forecasting the onion productions in Bangladesh is ARIMA (0,2,1). From the comparison between the original series and forecasted series shows the same manner indicating fitted model are statistically well behaved to forecast onion productions in Bangladesh i.e., the models forecast well during and beyond the estimation period to a satisfactory level.